Pengaruh Kombinasi Tapioka dan Tepung Kedelai terhadap Kualitas Sosis Ikan Kakap Putih (Lates calcarifer Bloch) - Prima Novi Agatha; Ekawati Purwijantiningsih; F. Sinung Pranata (Universitas Atma Jaya Yogyakarta, 2008)
Sausage is food product made from mix ture of minced meat (contain meat more than 75%), flour or starch with or without additional spices, and other allowed food additive. Sausage made from meat usually has a higher content of fat, which in many cases usually caused serious health problem. To reduce the fat content in sausages, the researchers try to combine cassava starch with soybean flour. Soybean flour was used in combination with cassava starch because it reduced of cholesterol in blood, reduced oil absorption while frying. Soybean flour is a kind of food material that has higher content of protein but low fat, and it has complete essential amino acids. This research was conducted to find out the influence of cassava starch and soybean flour combinations to produce good quality of seabass sausages. In this experiment, cassava starch and soybean flour combination were as follows 90:10; 80:20; and 70:30. The result showed that the combination of cassava starch with soybean flour increase water content, ash content, protein content and fat content but elasticity and carbohydrate content were decrease.